2021
DOI: 10.1186/s12909-021-02722-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Feedback Quality Instrument: a guide for health professional educators in fostering learner-centred discussions

Abstract: Background Face-to-face feedback plays an important role in health professionals’ workplace learning. The literature describes guiding principles regarding effective feedback but it is not clear how to enact these. We aimed to create a Feedback Quality Instrument (FQI), underpinned by a social constructivist perspective, to assist educators in collaborating with learners to support learner-centred feedback interactions. In earlier research, we developed a set of observable educator behaviours d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…The valid instruments available regarding the feedback in medical education are not used to assess the feedback received by the learners. This study assessed the quality of feedback from the viewpoint of residents and interns by FQI means, based on Johnson's claim that the original version of FQI was the most complete version of the feedback quality assessment tool (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The valid instruments available regarding the feedback in medical education are not used to assess the feedback received by the learners. This study assessed the quality of feedback from the viewpoint of residents and interns by FQI means, based on Johnson's claim that the original version of FQI was the most complete version of the feedback quality assessment tool (17).…”
Section: Discussionmentioning
confidence: 99%
“…The feedback quality instrument was designed by Johnson et al (2021). The manufacturer has authorized the use of the tool.…”
Section: Description Of the Toolmentioning
confidence: 99%
“…So, how can psychological safety be fostered? Our research on feedback discussions in clinical practice identified practical ways for supervisors to collaborate with junior clinicians to promote trust, respect, inclusion, and support, as well as reduce power imbalance 8,9 . Key to this is having a growth mindset, proposed by Dweck, 10 which endorses continuing development of skills.…”
Section: Introductionmentioning
confidence: 97%
“…Our research on feedback discussions in clinical practice identified practical ways for supervisors to collaborate with junior clinicians to promote trust, respect, inclusion, and support, as well as reduce power imbalance. 8,9 Key to this is having a growth mindset, proposed by Dweck, 10 which endorses continuing development of skills. This mindset accepts that mistakes are an inevitable part of learning and provide opportunities for enabling performance improvement.…”
mentioning
confidence: 99%